Faith-based HIV response in post-Soviet Eastern Europe: the case of Channels of Hope in Russia, Romania, and Armenia. Issue 5 (4th July 2017) - le Roux, Elisabet
ABSTRACT: Most of the data available on faith-based HIV response focus on Africa, which is the heart of the pandemic. This article investigates faith-based community-level HIV responses within Eastern Europe, by studying the implementation of World Vision International's "Channels of Hope" faith-based HIV intervention. The intervention approach was developed in a high HIV-prevalence setting (South Africa) and then implemented across sub-Saharan Africa and elsewhere – including three low HIV-prevalence Eastern European settings (Armenia, Romania, and Russia). Drawing from implementation and evaluation research, this article explores the nature, challenges, and potential of faith-based HIV response within low-prevalence, post-Soviet contexts.